2021
DOI: 10.3390/membranes11080552
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Polypropylene Membrane to Oil Fouling during Membrane Distillation

Abstract: The influence of oil emulsion presence in the water on the course of water desalination by membrane distillation was studied. The feed water was contaminated by oil collected from the bilge water. The impact of feed composition on the wetting resistance of hydrophobic polypropylene membranes was evaluated during long-term studies. Two types of the capillary membranes fabricated by thermally induced phase separation method were tested. It has been found that these membranes were non-wetted during the separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…The brines contaminated up to 100 mg/L of oil separated by the MD process conducted for several thousand hours showed a good wetting resistance of capillary PP membranes [ 11 , 33 ]. However, some unfavorable changes were noticed after several hundred hours of MD, when the concentration of NaCl in the feed was 300 g/L [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The brines contaminated up to 100 mg/L of oil separated by the MD process conducted for several thousand hours showed a good wetting resistance of capillary PP membranes [ 11 , 33 ]. However, some unfavorable changes were noticed after several hundred hours of MD, when the concentration of NaCl in the feed was 300 g/L [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the Accurel PP V8/2 polypropylene capillary membranes manufactured by Membrana GmbH (Wuppertal, Germany) were tested. These membranes are fabricated by thermally induced phase separation (TIPS) and exhibited a partial oleophobic performance [ 33 ]. The capillaries inner diameter and the wall thickness were equal to 5.5 mm and 1.5 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, in such cases, the oil concentration is much lower than that noted in produced water, and contamination occurs in the form of an emulsion containing oil droplets with a diameter below 50 µm [ 13 , 31 ]. The previously performed investigation [ 32 ] demonstrated that polypropylene (PP) membranes show wetting resistance by such solutions. With regard to PTFE membranes, in [ 8 ], it was observed that the wetting resistance increased with decreasing oil concentrations in the feed from 1000 to 100 mg/L.…”
Section: Introductionmentioning
confidence: 99%